2022
DOI: 10.26735/tnjt2900
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Influencing the Use of Password Managers

Abstract: This paper investigates the factors that influence the actual use of password managers. In this paper, we have integrated some factors from the Technology Acceptance Model (perceived ease of use, perceived usefulness, and attitude) with other factors from the literature review (user readiness, awareness, and motivation) to investigate the influence of these factors on the use of password managers. The authors used an online questionnaire to collect data. The questionnaire was distributed by using two social me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…This is consistent with [16], where they found that user readiness is a significant factor influencing the use of mobile technologies for learning purposes. In addition, this agrees with the findings reached by [6], where they found that user readiness has a significant influence on the use of password managers. The readiness to use cloud computing can be achieved by knowing and understanding the benefits of the use of this technology and its use method.…”
Section: A Discussion Of the Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This is consistent with [16], where they found that user readiness is a significant factor influencing the use of mobile technologies for learning purposes. In addition, this agrees with the findings reached by [6], where they found that user readiness has a significant influence on the use of password managers. The readiness to use cloud computing can be achieved by knowing and understanding the benefits of the use of this technology and its use method.…”
Section: A Discussion Of the Resultssupporting
confidence: 92%
“…Also, their awareness about this technology may lead them to understand how to avoid any harm that might result from using it. This argument is in alignment with number of studies such as [54], [53], and [6], where they have argued that awareness is considered a significant factor influencing the use of new technology. Thus, it is important for individuals to raise their awareness and improve their understanding of this technology, its use, and benefits so that they can use it effectively to utilize these benefits.…”
Section: A Discussion Of the Resultssupporting
confidence: 73%
See 3 more Smart Citations